Caregiver burden and quality of life among family caregivers of hemodialysis patients from South India - Afina Azeez; Srikant Ambatipudi (Journal of Education and Health Promotion)
BACKGROUND: Hemodialysis (HD) patients require assistance from family caregivers in performing daily activities. This additional responsibility may cause caregivers to feel burdened, resulting in a poor quality of life. The current study envisaged assessing the degree of caregiver burden (CB) and quality of life among the primary caregivers of HD patients. MATERIALS AND METHODS: A cross-sectional study was conducted among conveniently sampled, consenting family caregivers (N = 200) of HD patients in tertiary care dialysis centers in Thiruvananthapuram, Kerala, India, from March 2022 to May 2022. A structured interview schedule was used to collect sociodemographic data from participants. The caregiver burden and quality of life were assessed using the Zarit Burden Interview and the World Health Organization (WHO) Quality of Life (QoL) BREF scale. Univariate and multivariate analyses were performed to determine the association between the variables. RESULTS: Fifty-eight percent of the caregivers reported CB. Caregivers with no leisure time (ORadj = 3.29 [95% CI: 1.73–6.41]), perceived financial stress (ORadj = 2.27 [95% CI: 1.16–4.49]), and having comorbidities (ORadj = 2.92 [95% CI: 1.43–6.12]) had an increased odds of experiencing caregiver burden. The CB score was inversely correlated with all domains of QoL. Moreover, the QoL score was lower among family caregivers with CB than those without CB. CONCLUSION: The present study highlights a high prevalence of caregiver burden, which negatively impacts the QoL of family caregivers of HD patients. This study opens up new directions for possible policy-making to reduce caregiver burden and improve the QoL of family caregivers.